2020
DOI: 10.3389/fpsyt.2020.591120
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Social Isolation with Anxiety and Depression During the Early COVID-19 Pandemic: A Survey of Older Adults in London, UK

Abstract: The COVID-19 pandemic is imposing a profound negative impact on the health and wellbeing of societies and individuals, worldwide. One concern is the effect of social isolation as a result of social distancing on the mental health of vulnerable populations, including older people. Within six weeks of lockdown, we initiated the CHARIOT COVID-19 Rapid Response Study, a bespoke survey of cognitively healthy older people living in London, to investigate the impact of COVID-19 and associated social isolation on ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
313
6
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(363 citation statements)
references
References 48 publications
26
313
6
18
Order By: Relevance
“…Our findings also have specific relevance to the social context of the COVID-19 pandemic, echoing some previous studies. For example, one cross-sectional study of 7127 UK older adults aged 70 on average who self-reported whether their mental health had changed, found that loneliness was associated with reporting a worsening of depression and anxiety symptoms, although this study did not objectively identify change in mental health (Robb et al, 2020 ). In our study, the association was relatively modest; the minimum difference on the PHQ-9 considered to indicate a clinically meaningful improvement in response to treatment being between 2.8 and 5 points (Löwe, Unützer, Callahan, Perkins, & Kroenke, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also have specific relevance to the social context of the COVID-19 pandemic, echoing some previous studies. For example, one cross-sectional study of 7127 UK older adults aged 70 on average who self-reported whether their mental health had changed, found that loneliness was associated with reporting a worsening of depression and anxiety symptoms, although this study did not objectively identify change in mental health (Robb et al, 2020 ). In our study, the association was relatively modest; the minimum difference on the PHQ-9 considered to indicate a clinically meaningful improvement in response to treatment being between 2.8 and 5 points (Löwe, Unützer, Callahan, Perkins, & Kroenke, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, social isolation which took place during lockdown may have also had a significant effect in overall mental health. The effect of social isolation on mental health is evident through numerous studies and has already raised significant concerns [ 24 , 25 , 26 ]. It is argued that negative mental health impacts do not simply stop but continue following the lockdown period [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that there may be an increased need for assessment of new patients in geriatric psychiatry settings as a result of the negative consequence of quarantine and social distancing measures. In fact, psychological symptoms due to stressor events can contribute to cognitive decline (20) and social isolation, reduced social network, and loneliness can lead to generalized anxiety and major depression disorders in older individuals (21)(22)(23). Further, during lockdown it is likely that many older persons reduced their physical activity levels (5), which may impair symptoms; for example, cardiorespiratory fitness is also associated with cognitive functioning in older persons (24).…”
Section: Discussionmentioning
confidence: 99%